Open-channel microfluidic chip based on shape memory polymer for controllable liquid transport. Issue 8 (16th March 2023) - Ye, Wen-Qi; Liu, Xiao-Peng; Ma, Ruo-Fei; Yang, Chun-Guang; Xu, Zhang-Run
Abstract : Controllable liquid transport through the deformation of shape memory microcolumns in an open-channel microfluidic chip. Abstract : Open microfluidics has attracted increasing attention over the last decade because of its flexibility and simplicity with respect to cell culture and clinical diagnosis. However, traditional valves and pumps are difficult to integrate on open-channel microfluidic chips, in which a liquid is usually driven by capillary forces. Poor fluid control performance is a common drawback of open microfluidics. Herein, we proposed a method for controlling the liquid flow in open channels by controlling the continuous Laplace pressure induced by the deformation of the shape memory microstructures. The uniformly arranged cuboidal microcolumns in the open channels have magnetic/light dual responses, and the bending angle of the microcolumns can be controlled by adjusting Laplace pressure using near-infrared laser irradiation in a magnetic field. Laplace pressure and capillary force drove the liquid flow together, and the controllable fluid transport was realized by adjusting the hydrophilicity of the channel surface and the bending angle of the microcolumns. We demonstrated the controllability of the flow rate and the directional transport of water along a preset path. In addition, the start and stop of water transport were realized via local hydrophobic modification. The proposed strategy improves poor fluid control in traditional open systems and makes fluid flow highly controllable. We tried to extract and detect rhodamine B in tiny droplets on the open microfluidic chip, demonstrating the advantages of the proposed strategy in the separation and analysis of tiny samples.